If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 5 * 3x + -2 = 0 Multiply 5 * 3 X + 15x + -2 = 0 Reorder the terms: -2 + X + 15x = 0 Solving -2 + X + 15x = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '2' to each side of the equation. -2 + X + 2 + 15x = 0 + 2 Reorder the terms: -2 + 2 + X + 15x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + X + 15x = 0 + 2 X + 15x = 0 + 2 Combine like terms: 0 + 2 = 2 X + 15x = 2 Add '-15x' to each side of the equation. X + 15x + -15x = 2 + -15x Combine like terms: 15x + -15x = 0 X + 0 = 2 + -15x X = 2 + -15x Simplifying X = 2 + -15x
| (3-5x)/(2x-4)=0 | | 2x+3x=15findx | | 18x^2/10y^2*15y^3/24x | | 23-2=x-2+7 | | -2+2w=-4 | | 5(x+5)=7(2x-6) | | x/5-5=15 | | -x+x+5=0 | | (X+5)=7(2x-6) | | 6(3s+6)=54 | | 11m+1=8m+4 | | 6y-2=4y+14 | | 3(x+5)+5+1=31 | | -2(4x-9)=10 | | 12x-4+x=180 | | 9d^2+3d-5=0 | | 8(3m-2)=104 | | 41=6v-7 | | 42y-42y^2=20 | | (2x-1)(x+2)+(3x+1)(x-1)= | | 3(n+4)-8=11-(6-2n)52 | | 3*(2x-1)=9 | | 8x-2y=60 | | 7/(10x)=103/20 | | 4x=8x+32 | | x-0.7=5.5 | | 7x3/6 | | x*2x=50000 | | 3(2b-1)=27 | | 1/8x-1/8y=19 | | log(12)2+log(12)x=log(12)(x+7) | | 2x^3+12=0 |